2012
DOI: 10.1111/j.1365-2850.2012.01902.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding aggressive behaviour across the lifespan

Abstract: Aggressive behavior is the observable manifestation of aggression and is often associated with developmental transitions and a range of medical and psychiatric diagnoses across the lifespan. As healthcare professionals involved in the medical and psychosocial care of patients from birth through death, nurses frequently encounter—and may serve as—both victims and perpetrators of aggressive behavior in the workplace. While the nursing literature has continually reported research on prevention and treatment appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
110
1
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 112 publications
1
110
1
13
Order By: Relevance
“…The differences in subscale effect sizes suggest that the effects of AASs are likely to be somewhat idiosyncratic, with a wide variety of non-AAS influences (Liu, Lewis, & Evans, 2013). The majority of participants in this study were middle aged men and we did not assess for lifetime aggressive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in subscale effect sizes suggest that the effects of AASs are likely to be somewhat idiosyncratic, with a wide variety of non-AAS influences (Liu, Lewis, & Evans, 2013). The majority of participants in this study were middle aged men and we did not assess for lifetime aggressive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…6 Aggressive behavior is also a key precursor to many mental illnesses, including antisocial personality disorder. 7 Although genetic factors are important causes of aggressive behaviors, environment also accounts for 50% of its total variance.…”
Section: Introductionmentioning
confidence: 99%
“…We define aggression in this paper as an expressed negative and destructive emotion (e.g., expression of anger, frustration, and sorrow) in the form of directly or indirectly inflicted self-harm in addition to intentional or unintentional physical, verbal, and nonverbal acts that often result in injury, death, psychological harm, maldevelopment or deprivation (Blake & Hamrin, 2007; Liu, Lewis & Evans, In press; WHO, 2002). …”
Section: Childhood Aggressionmentioning
confidence: 99%
“…Olweus (1979) reported an average correlation of 0.63 (0.79 after correcting for attenuation) between early aggression in childhood or adolescence and later aggression, and longitudinal studies have consistently documented that problem behavior in childhood is predictive of adolescent and adult behavior (e.g., Broidy et al, 2003; Farrington, 2003). In particular, it has been associated with alcohol and drug abuse, criminal behavior, academic failure, antisocial behavior, behavioral issues, depression, suicide, family dysfunction, domestic abuse, injury, neglectful and abusive parenting, and even death (Liu, 2004; Liu, Lewis & Evans, In press). A recent 40-year longitudinal study also showed that these negative outcomes tend to be more problematic for life-course-persistent aggressives (onset in early childhood) than late-onset (early adulthood) aggressives (Huesmann, Dubow, & Boxer, 2009).…”
Section: Childhood Aggressionmentioning
confidence: 99%